Fatty acid, triacylglycerol composition and antioxidant properties of date seed oil - Mohd Jaih, Abdul Afiq; Abdul Rahman, Russly; Abdull Razis, Ahmad Faizal; Ariffin, A. A.; Al-Awaadh, A.; Suleiman, N. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Oil is one of the major components of date seed alongside dietary fibre, carbohydrate, protein, moisture and ash. Therefore, the present work focused on the extraction of oil from five varieties of date seed using Soxhlet extraction method and subsequently characterised their physicochemical and antioxidant properties accordingly. Oil extracted from the seeds ranged between 8 to 9.8%, whereas the iodine values were between 48.7 to 55.5 g I2/100g. Furthermore, oleic and lauric acids were revealed as the main fatty acids present in the date seed oil, with LaOO (La: lauric acid; O: oleic acid) as the main triacylglycerol. The total phenolic content in the oil ranged from 7.96 to 17.72 mg GAE/g oil, while the antioxidant activity, expressed as EC50, ranged from 5.17 to 17.18 mg/mL. Additionally, the highest reducing activity was observed at 4mg/mL. Hence, oil characteristics are dependent on the type of date, thus indicating that different potential applications may be suggested.